Effects of compressive stress on dielectric properties of lead-free (Bi1/2Na1/2)TiO3-(K1/2Na 1/2)NbO3 ceramic systems - Thanapong Sareein (2018)
Lead-free, bismuth sodium titanate-potassium sodium niobate piezoelectric ceramics (Bi1/2Na1/2)TiO3-(K 1/2Na1/2)NbO3 have been prepared by a conventional mixed-oxide method via vibro-milling technique. The (K 1/2Na1/2)NbO3 (KNN)-based compositions with a morphotropic phase boundary (MPB) have shown greater advantages over another typical lead-free piezoelectric candidate material system, (Bi 1/2Na1/2)TiO3 (BNT)-based MPB materials. More importantly, when used this type of material is often subjected to self-induced or external stress. It is, therefore, of interest to investigate influence of stress on properties of the ceramics. In this study, the influences of compressive stress on the dielectric properties of BNT-KNN ceramics were investigated. The dielectric properties were determined under compressive stress applied parallel to electric field. The results indicate significant changes of both properties with the imposed compressive stress. The results were explained in terms of non-180° domain switching and de-aging of the dielectric properties under the influence of the applied stress. © (2010) Trans Tech Publications.